2012
DOI: 10.1016/j.jenvman.2012.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sawdust addition on composting of separated raw and anaerobically digested pig manure

Abstract: Comparison of GI at day 56 was performed using the MIXED procedure in SAS. initial heating phase, a thermophilic phase, and cooling/maturing phase (Figure 1(a) and (b)). 246The patterns of compost temperature change have been used to monitor the stabilization of the 247 composting process (Tiquia et al., 1996; Huang et al., 2004; Tiquia, 2005 The pH values followed a similar pattern for all treatments (Figure 2 (a) and (b) Treatments B and C were within the limits. Tiquia et al. (1996) found that a WC of 70 % Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…2a) are within the desirable range of 6 -8 for composting (Bustamante et al, 2008;Troy et al, 2012), and the rapid increase in the initial 15 days could be attributed to the degradation of acid-type compounds and the mineralization of proteins, amino acids and peptides to ammonia. Then the pH values tended to be stable at 7.50-8.50…”
Section: Changes Of Temperature Ph and Moisturementioning
confidence: 93%
“…2a) are within the desirable range of 6 -8 for composting (Bustamante et al, 2008;Troy et al, 2012), and the rapid increase in the initial 15 days could be attributed to the degradation of acid-type compounds and the mineralization of proteins, amino acids and peptides to ammonia. Then the pH values tended to be stable at 7.50-8.50…”
Section: Changes Of Temperature Ph and Moisturementioning
confidence: 93%
“…Despite the rapid temperature decline, the authors indicated the final compost in the laboratory trial was hygienically acceptable (Franke-Whittle et al, 2014). Turning is also used to provide oxygen and to homogenize composting materials (Troy et al, 2012). For composting of AD effluent with bulking agents, the overall moisture content is normally maintained above 40% to support microbial growth.…”
Section: Compostingmentioning
confidence: 99%
“…After an initial heating period of 4-5 days, the temperature of the CM, DCM, CW, TSW, GW, and KW quickly reach 50-60°C. Troy et al (2012) reported that this quick rise in temperature was due to the degradation of sugars, proteins and fats by microbial activity; this degradation resulted in heat generation. The MSW pile reached 50°C on day 8, which was much later than the other groups.…”
Section: Physical-chemical Analysismentioning
confidence: 99%